The energy use of biogas as a tool for the goals of sustainable development - Lins, Leonardo Pereira (2022)
The global demand for energy and food generates, both in the countryside and in the city, environmental impacts, and many of these are due to the poor disposal of organic waste. One way to minimize these impacts on the environment is to carry out the treatment of waste generated in the various sectors. Among the possibilities for treating organic waste is anaerobic digestion. After this process, there is the production of biogas, which is composed of several gases, including methane and carbon dioxide as the main ones. Biogas has energy potential, being able to generate electrical and thermal energy, in addition to being used in the form of biomethane. With the diversity of energy applications and the possibility of reducing waste, both anaerobic digestion and biogas contribute to the implementation and application of the Sustainable Development Goals (SDGs). These goals have a wide scope, ranging from the need for basic sanitation, clean and accessible energy for all, sustainable cities and communities, responsible consumption, to actions against global climate change, through the reduction of greenhouse gases. The objective of this work is to relate the SDGs and the anaerobic digestion of organic waste projects, which contribute both to the significant improvement of a community or region, as well as to environmental, social, and economic issues. The methodology used was the analysis of the concepts served by the use of the anaerobic digestion system in accordance with the objectives, goals, and sub-targets of the SDGs. The interrelation of at least five SDGs was observed: 6, 7, 11, 12, and 13. The use of anaerobic systems with the use of biogas helps in the substitution and/or reduction of energy sources not renewable resources, which can be applied both in the city and in the countryside, promoting a better quality of life for all.